Emotional intelligence of the teacher and academic satisfaction of the university student - Tacca Huamán, Daniel Rubén (2020)
In the XXI century, the university professor has become a mediating agent between the student and knowledge; in addition, the personal and professional skills of university professors are actively involved in student learning. The purpose of the research was to know the relation between the emotional intelligence of university professors (Bar-On model) and the academic satisfaction of university students, seen as part of the psychological well-being (eudaimonic position). The research was correlational and transversal, emotional intelligence was assessed to 87 professors and information on academic satisfaction was collected in 597 students. The results indicated that the study variables correlate positively (.80), being the interpersonal component to have the highest correlation coefficient with the academic satisfaction. Further-more, it was observed that 91% of professors obtained average and high levels of emotional intelligence; women professors obtained higher scores than men professors, but the differences were not significant. Additionally, professors over 45 years of age showed greater development of emotional skills and greater academic satisfaction from the students.